2013
DOI: 10.1177/0042098013505887
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of LRT, Neighbourhood Characteristics, and Self-selection on Auto Ownership: Evidence from Minneapolis-St. Paul

Abstract: There is a growing interest in exploring the relationships between the built environment and auto ownership and a number of studies have investigated the impact of rail transit on travel behaviour. However, few have disentangled the impact of rail transit on auto ownership from the influences of the built environment and residential self-selection. Using the light rail transit (LRT) in the Minneapolis-St. Paul metropolitan area, USA, this study applies the statistical control approach and quasilongitudinal des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…Another hotspot of public transit research is rail transit. Based on the same general argument as with bus stops, highly accessible stations lead residents to switch to rail transit and reduce local emissions in the process [51][52][53]. However, in this case too, some studies have found that this mode-shifting effect does not exist, especially for cars [54].…”
Section: Distance To Transitmentioning
confidence: 99%
“…Another hotspot of public transit research is rail transit. Based on the same general argument as with bus stops, highly accessible stations lead residents to switch to rail transit and reduce local emissions in the process [51][52][53]. However, in this case too, some studies have found that this mode-shifting effect does not exist, especially for cars [54].…”
Section: Distance To Transitmentioning
confidence: 99%
“…Apart from the aforementioned characteristics, attitude and preference characteristics have received more attention recently as self-selection effects [41,[45][46][47][48]. A variety of outcomes from self-selection effect have been empirically examined, ranging from travel model choice [47,[49][50][51]] to transportation energy consumption and emissions [41,45].…”
Section: Other Factors Influencing Car Ownership and Usementioning
confidence: 99%
“…An analysis of the sort conducted in this paper can be used to inform the task of using one or more LPGs to attract members of the creative class in actual cities of the sort delineated in the first paragraph of Section 2. In this regard, Cao and Cao (2014) show that the light rail transit (LRT) system has been important in impacting residents positively in the Minneapolis and Saint Paul metropolitan area. As such, apposite city officials in these two cities can…”
Section: Discussionmentioning
confidence: 99%